Considerations and barriers to starting a new HAI pump program: an international survey of the HAI Consortium Research Network. Issue 12 (December 2022) - Cavnar, Michael; Ghalambor, Tara; Lidsky, Michael E.; Dominguez-Rosado, Ismael; Cho, May; Karanicolas, Paul; Merkow, Ryan; Mayo, Skye C.; Rocha, Flavio G.; Fields, Ryan C.; Koerkamp, Bas G.; Yopp, Adam; et al.
Abstract: Background: Widespread implementation of HAI pump chemotherapy has been limited by logistic and feasibility concerns. Recent studies demonstrating excellent outcomes have fueled renewed enthusiasm and multiple new programs have emerged. This survey aims to identify barriers critical to establish a successful HAI program. Methods: Using SurveyMonkey™, a 17-question survey assessing factors required for establishing a successful program was developed by 12 HAI Consortium Research Network (HCRN) surgical oncologists. Content analysis was used to code textual responses. Frequency of categories and average rank scores for each choice were calculated. Results: Twenty-eight HCRN members responded to the survey. Implementation time varied, with 15 institutions requiring less than a year. Most programs (n = 17) became active in the past 5 years. Medical and surgical oncology were ranked most important for building a program (average ranking scores: 7.96 and 6.59/8). Administrative or regulatory approval was required at half of the institutions. The top 3 challenges faced when building a program were related to regulatory approval (6.65/9), device/equipment access (6.33/9), and drug (FUDR) access (6.25/9). Conclusion: Development of successful programs outside of historically established centers is feasible and requires a multidisciplinary team. Future collaborative efforts are critical for sustainability of safe/effective new programs.